2019
DOI: 10.1016/j.heliyon.2019.e01536
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review of fenugreek seed toxicity by using ToxRTool: evidence from preclinical and clinical studies

Abstract: Fenugreek (Trigonella foenum graecum) seed extract is a bioactive ingredient of many food supplements. Hence, there is a need for systematic assessment of the quality of published toxicological studies for its use in human health, hazard consideration, and risk assessment. The aim of the present investigation was to determine the reliability of published toxicological studies of fenugreek seed by using ToxRTool (Toxicological data reliability assessment tool). A comprehensive systematic literature search was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 53 publications
0
65
0
Order By: Relevance
“…Consistent with published clinical data regarding N. sativa and fenugreek in combination or alone, the consumption of NFC had no adverse effect on hepatic, kidney, or thyroid functioning. 15,28,60,61 While in vitro and animal studies describe the potential for an interaction of N. sativa or fenugreek phytoceuticals with drugs metabolized by hepatic CYP3A4, 62,63 in our study one subject receiving metoprolol (a CYP3A4 substrate) therapy for hypertension maintained readings of 120, 80, 40, and 93 mmHg for SBP, DBP, PP, and MAP, respectively, from baseline through 12 weeks.…”
Section: Safetymentioning
confidence: 71%
“…Consistent with published clinical data regarding N. sativa and fenugreek in combination or alone, the consumption of NFC had no adverse effect on hepatic, kidney, or thyroid functioning. 15,28,60,61 While in vitro and animal studies describe the potential for an interaction of N. sativa or fenugreek phytoceuticals with drugs metabolized by hepatic CYP3A4, 62,63 in our study one subject receiving metoprolol (a CYP3A4 substrate) therapy for hypertension maintained readings of 120, 80, 40, and 93 mmHg for SBP, DBP, PP, and MAP, respectively, from baseline through 12 weeks.…”
Section: Safetymentioning
confidence: 71%
“…(2019), part of the conflicting evidence may be related to the quality and reliability of the published toxicological studies, which have seldom been assessed. Their systematic review identified 17 toxicological studies classified as category 1 (“reliable without restrictions”), consisting of animal studies, preclinical, and clinical trials, mostly published after 2010, that consistently suggested that fenugreek seeds are safe and well tolerated (Kandhare et al., 2019). Considering the digestive, neurophysiological, and reproductive side effects reported in some studies, Ouzir et al.…”
Section: Toxicology and Safety Profile Of Fenugreekmentioning
confidence: 99%
“…Using a recent assessment tool, ToxRTool, a toxicological data reliability assessment tool, (Schneider et al., 2009), to test the reliability of toxicological data, Kandhare, Thakurdesai, Wangikar, and Bodhankar (2019) identified 17 studies indicating that fenugreek seeds have a broad margin of safety and that these studies are “reliable without restrictions”. In a review Alves‐Silva, Romane, Efferth, and Salgueiro (2017) of fenugreek trials in humans, no adverse effects were reported when fenugreek or its extract was administered orally (up to 5 g kg –1 bodyweight) up to various lengths of time (14 d–24 wk), with the exception of minor gastrointestinal disturbances in a few test subjects.…”
Section: Role Of Sainfoin and Fenugreek In Human Healthmentioning
confidence: 99%